2009
DOI: 10.1007/s10919-008-0065-7
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing Emotions in a Foreign Language

Abstract: Expressions of basic emotions (joy, sadness, anger, fear, disgust) can be recognized pan-culturally from the face and it is assumed that these emotions can be recognized from a speaker's voice, regardless of an individual's culture or linguistic ability. Here, we compared how monolingual speakers of Argentine Spanish recognize basic emotions from pseudo-utterances (''nonsense speech'') produced in their native language and in three foreign languages (English, German, Arabic). Results indicated that vocal expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
157
3
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 268 publications
(188 citation statements)
references
References 34 publications
21
157
3
7
Order By: Relevance
“…In this study, we investigate whether certain nonverbal emotional vocalizations communicate the same affective states regardless of the listener's culture. Currently, the only available cross-cultural data of vocal signals come from studies of emotional prosody in speech (6)(7)(8). This work has indicated that listeners can infer some affective states from emotionally inflected speech across cultural boundaries.…”
mentioning
confidence: 99%
“…In this study, we investigate whether certain nonverbal emotional vocalizations communicate the same affective states regardless of the listener's culture. Currently, the only available cross-cultural data of vocal signals come from studies of emotional prosody in speech (6)(7)(8). This work has indicated that listeners can infer some affective states from emotionally inflected speech across cultural boundaries.…”
mentioning
confidence: 99%
“…Much of the emotional quality of the human voice can be inferred by the physical features of the vocalisation, and by the sonic properties of one's speech. Nonverbal expressions, for example, communicate affective meaning and information about the speaker's state of mind independently of linguistic cues, as shown by cross-cultural studies (Scherer et al, 2001;Pell et al, 2009). The human auditory system is especially sensitive to the human voice.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, few investigations have attended to social psychological factors that could potentially influence emotional speech recognition. Exceptions to this come from research on the moderating role of cultural background (e.g., Paulmann & Uskul, 2014;Pell, Monetta, Paulmann & Kotz, 2009;Scherer et al, 2001), sex (e.g., Schirmer, Kotz, & Friederici, 2002) and age (e.g. Paulmann et al, 2008;Kiss & Ennis, 2001) in emotional prosody processing.…”
mentioning
confidence: 99%